2011
DOI: 10.2134/agronj2011.0060
|View full text |Cite
|
Sign up to set email alerts
|

Forage, Nitrogen, and Phosphorus Yield Dynamics of Cool‐Season Annual Forages Overseeded onto Tifton 85 Bermudagrass

Abstract: MATERIALS AND METHODSAn on-dairy trial was performed from 2005 to 2007 near Dublin, TX (32°15' N, 98°12' W, altitude 395 m) on an established 5-yr-old stand of Tift on 85 with a history of dairy manure application. Th e soil in the experiment area was a Windthorst fi ne sandy loam (pH 7.7, 83 mg P kg -1 , 249 mg K kg -1 , 1770 mg Ca kg -1 , and 147 mg Mg kg -1 using the Mehlich III extractant method; Mehlich, 1984). Th ese values were stable from year to year. Adjacent but distinct experiment sites under the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 22 publications
2
14
0
Order By: Relevance
“…Except for N fertilizer in 2009-2010, grass-hairy vetch mixtures yielded greater DM than other treatments when averaged over all grass entries in the forage harvest both years. Other studies reported greater hairy vetch forage yields when overseeded as a monoculture into dormant bermudagrass compared with similar annual cool-season legumes, except during dry spring conditions (Muir and Bow, 2011;Freeman et al, 2016). In our study, plots containing hairy vetch had forage yields 40 and 290% greater than crimson clover and the control, respectively, in 2009-2010.…”
Section: Dry Matter Yield: Legumes or Fertilizersupporting
confidence: 40%
See 3 more Smart Citations
“…Except for N fertilizer in 2009-2010, grass-hairy vetch mixtures yielded greater DM than other treatments when averaged over all grass entries in the forage harvest both years. Other studies reported greater hairy vetch forage yields when overseeded as a monoculture into dormant bermudagrass compared with similar annual cool-season legumes, except during dry spring conditions (Muir and Bow, 2011;Freeman et al, 2016). In our study, plots containing hairy vetch had forage yields 40 and 290% greater than crimson clover and the control, respectively, in 2009-2010.…”
Section: Dry Matter Yield: Legumes or Fertilizersupporting
confidence: 40%
“…Nitrogen fertilizer applied to cool-season grasses harvested as forage resulted in the greatest spring first-cut Tifton 85 DM yield. This may indicate residual soil N or less spring competition for soil moisture and solar irradiation in the absence of legumes, as is reported in legume-monoculture studies by Freeman et al (2016) and Muir and Bow (2011), in which spring first-harvest bermudagrass yields were lower when overseeded with cool-season legumes the preceding winter compared with no-legume controls. Research by Han et al (2012) (Muir and Bow, 2011).…”
Section: Tifton 85 Spring First-cut Dry Matter Yield With Spring N Fementioning
confidence: 57%
See 2 more Smart Citations
“…The other legumes maintained their DM yield into sequence 3 and did not senesce as rapidly. The literature reports both lower (Muir and Bow, 2011) and higher (Brink et al, 2001) yields for the same species of legumes. Chamblee and Mueller (1999) obtained yields of 4685 kg/ha for CC, 2903 kg/ha for AC, and 4303 kg/ha for HV, similar to those seen in this study, suggesting the yields we obtained are typical.…”
Section: Introductionmentioning
confidence: 95%